Technological Solution in Real Time Based on IoT Devices to Optimize Soccer Team Training - Macuri, Hiro (2024)
Currently, the soccer players of the youth clubs of the university community are engaged in constant physical training to improve their skills before an official match, requiring technological tools to man- age the physical preparation of each soccer player. For this reason, in this scientific article a technological solution will be proposed to optimize the training of soccer teams using IoT devices in real time. Its design based on technological architectures will be explained to detail the flow of the system and the components to be used to carry out the development and programming of the solution. Therefore, the functionality of the system will be validated based on 2 types of indicators based on the use of the solution in reality. The test indicators establish both the percentage of improvement in the level of physical performance of the amateur player for each weekly training session, as well as the weekly comparison of high performance levels of the amateur with a recognized and referential elite soccer player; all this to verify if the amateur is already physically pre- pared to play a championship. On the other hand, a series of questions were asked about the viability of the solution to interview selected users and experts, whose answers were finally mostly satisfactory.